Longer Interpregnancy Interval Is Associated with Gestational Diabetes Mellitus Recurrence - Peled, Tzuria; Federmesser, Daniella; Mazaki, Eyal; Sela, Hen Y.; Grisaru-Granovsky, Sorina; Rottenstreich, Misgav (American Journal of Perinatology, 2024)
This study aimed to evaluate the effect of interpregnancy interval (IPI) on the gestational diabetes mellitus (GDM) recurrence rate in the subsequent pregnancies following an initial pregnancy complicated by GDM.A multicenter, retrospective cohort study was conducted. The study included women diagnosed with GDM during their index pregnancy who subsequently delivered between 26 and 42 weeks of gestation from 2005 to 2021. The study population was categorized into eight groups according to their IPIs: up to 3, 3–5, 6–11, 12–17, 18–23, 24–35, 36–47, and over 48 months. We examined the recurrence rate of GDM in the different groups while comparing it to the 18–23-month group that was defined as the reference group. Statistical analyses included univariate analyses and multiple logistic regression.Out of 3,532 women who were included in the study, 1,776 (50.3%) experienced GDM recurrence in subsequent pregnancy. The recurrence rate was 44.6% for women IPI <6 months, 42.6% for women IPI of 6–11 months, 48.0% for women IPI of 12–17 months, 49.7% for women IPI of 18–23 months, 58.0% for women IPI of 24–47 months, and 62.6% for women IPI above 48 months. Multivariable logistic regression revealed that IPIs of 24–47 months and over 48 months were significantly associated with higher recurrence rates as compared with the 18–23-month reference group (adjusted odds ratio [aOR], 95% confidence interval [CI]: 1.66 [1.04–2.64] and 3.15 [1.07–9.29], respectively). This analysis also revealed other independent risk factors for GDM recurrence, including medication-controlled GDM in the index pregnancy, obesity, maternal age, parity, and gravidity.Longer IPIs (over 24 months) are associated with an increased risk of GDM recurrence in subsequent pregnancies. These findings suggest that clinicians should consider IPI while managing postpartum care and planning future pregnancies for women with a history of GDM.
Keywords: gestational diabetes; interpregnancy interval; recurrence; postpartum management; obesity; maternal age